(untitled) (Journal of Economic Research & Business Administration, 2015)
In the article the substantive distinction between social and technical innovations are found in their immaterial intangible structure. While the changed and intensified social and economic problems identified in public discourse are increasingly prompting a call for extensive social inn ovation, the topic continues to remain a largely under - explored area in the social sciences as well as government innovation policies.